2002
DOI: 10.1007/s00432-002-0351-4
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between hematopoietic progenitor cell counts as measured by Sysmex and CD34+ cell harvest yields following mobilization with different regimens

Abstract: Lymphoma and multiple myeloma patients who were moderately pretreated and mobilized with chemotherapy and G-CSF showed the best results in correlation analyses even at low HPC counts. Therefore, HPC measurement can be used for timing of apheresis in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…It is interesting that the HPC method correlated well with the standard CD34 + cell determination in the peripheral blood but the HPC count agreed only weakly with the reference method in the collection product ( R = 0.464) and similar results have been reported by Vogel et al [28]. Our group of patients was relatively small and it is possible that the correlation index could increase if more patients are used.…”
Section: Discussionsupporting
confidence: 86%
“…It is interesting that the HPC method correlated well with the standard CD34 + cell determination in the peripheral blood but the HPC count agreed only weakly with the reference method in the collection product ( R = 0.464) and similar results have been reported by Vogel et al [28]. Our group of patients was relatively small and it is possible that the correlation index could increase if more patients are used.…”
Section: Discussionsupporting
confidence: 86%
“…Previous comparisons of HPC analysis by Sysmex SE and XE series analyzers with CD34+ cell counting showed only moderate correlations, 19,20 and the relationship between preharvest peripheral blood HPC counts and CD34+ yields in apheresis products was not strong. 31 Although high peripheral blood HPC counts were useful for determining when to initiate stem cell collection, low HPC counts (<5 × 10 6 /L) often underestimated peripheral blood CD34+ cells, and thus CD34 analysis was required.…”
Section: Discussionmentioning
confidence: 78%
“…17-19 Although HPC appears to be a useful positive predictor of when to initiate apheresis to obtain desired CD34+ cell yields, HPC levels below predefined cutoffs have not reliably predicted poor CD34+ cell collections. The latter has limited the use of HPC as a surrogate for CD34 analysis in PBSCT.…”
mentioning
confidence: 99%
“…The HPC count can be rapidly, simply and cost-effectively obtained by using the IMI channel of the automated hematology analyzer. However, the correlation of the HPC count in the peripheral blood with the number of CD34+ cells in the peripheral blood or in the apheresis yields has differed among reports (r = 0.556–0.88 and 0.62–0.762, respectively) [8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18]. The discrepancy might have resulted from differences in the conditions of storage of blood samples, which is not described in great detail in these reports.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we and others have reported that the HPC count monitored by an immature information (IMI) channel of the SE-9000 or SE-9500 hematology analyzer (TOA Medical Electronica, Kobe, Japan) is an alternative indicator of the optimal timing for apheresis procedures [8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18]. The HPC count can be rapidly, simply and cost-effectively obtained by using the IMI channel of the automated hematology analyzer.…”
Section: Introductionmentioning
confidence: 99%